Composite diaphragm based on super-hydrophilic electrostatic self-assembly material and preparation method thereof

By combining the ultra-hydrophilic electrostatic self-assembly material with the sulfonated polymer grid support layer, the problems of high resistance, poor hydrophilicity and easy filler fallout of the alkaline water electrolytic cell separator are solved, and efficient water electrolytic performance and long-life separator are achieved.

CN120330798APending Publication Date: 2025-07-18BEIJING UNIV OF CHEM TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510606935.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-12
Publication Date
2025-07-18

AI Technical Summary

Technical Problem

The existing alkaline water electrolytic cell separators have problems such as large resistance of polyphenylene sulfide fabrics, high energy consumption, poor hydrophilicity of composite separators, and easy to fall off inorganic fillers, which affects the electrolytic efficiency and separator life.

Method used

Using ultra-hydrophilic electrostatic self-assembly materials, by electrostatically self-assembling positively charged inorganic nanoparticles and negatively charged inorganic nanoparticles, combined with the sulfonated polymer grid support layer, a composite separator is prepared to enhance mechanical strength and hydrophilicity and reduce the shedding of inorganic fillers.

Benefits of technology

The prepared composite separator has excellent pore structure and surface hydrophilicity, good thermal stability and mechanical strength. It can be sustained and stable electrolysis in a high-temperature alkaline electrolyte environment for more than 300 hours, meeting industrial needs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120330798A_ABST
    Figure CN120330798A_ABST
Patent Text Reader

Abstract

The invention discloses a composite diaphragm based on a super-hydrophilic electrostatic self-assembly material and a preparation method of the composite diaphragm. The method comprises the following steps: dropwise adding positively charged inorganic nanoparticle dispersion liquid into negatively charged inorganic nanoparticle dispersion liquid, stirring for 1-3 hours, carrying out electrostatic self-assembly to obtain a composite material, centrifuging, drying, grinding, adding into a polymer solution, and carrying out ultrasonic stirring to obtain uniform membrane casting liquid; and blade-coating the membrane casting solution on two sides of the sulfonated high-molecular polymer grid supporting layer, and solidifying to form a membrane through pre-evaporation and phase inversion processes, thereby obtaining the composite membrane of the super-hydrophilic electrostatic self-assembly material. The obtained composite diaphragm has an excellent pore structure and surface hydrophilicity, good thermal stability and mechanical strength, can be continuously and stably electrolyzed for more than 300 hours under the current density of 500 mA. Cm <-2 >, can tolerate a high-temperature alkaline electrolyte environment for a long time, has good water electrolysis performance, can play a role for a long time, is long in service life, and meets the actual industrial requirements.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of alkaline water electrolysis for hydrogen production, and specifically relates to a composite diaphragm based on superhydrophilic electrostatic self-assembly materials and a preparation method thereof. Background Art

[0002] With the increase in the global population and the acceleration of the industrialization process, the demand for energy has been continuously climbing. At present, non-renewable fossil fuels such as coal, oil, and natural gas can no longer meet the needs of the sustainable development of human society. Therefore, it is imperative to develop new energy to replace traditional fossil fuels. As a clean and efficient energy carrier, hydrogen energy is regarded as one of the most likely energy sources to replace fossil fuels in the future due to its unique characteristics such as zero pollution, high efficiency, abundant supply, and wide application range.

[0003] Water electrolysis is considered to be the most promising hydrogen production strategy driven by renewable energy. As a green and carbon-free hydrogen production process, water electrolysis can produce ultra-high purity (99.9%) hydrogen, so it has attracted more and more attention from researchers. At present, the hydrogen production technology by electrolyzing water can be roughly divided into four types based on different electrolytes in the electrolysis process, namely solid oxide electrolysis water technology, proton exchange membrane electrolysis water technology, anion exchange membrane electrolysis water technology, and alkaline water electrolysis technology. Among them, the anion exchange membrane electrolysis water and solid oxide electrolysis water technologies are not yet mature. The proton exchange membrane electrolysis water technology inevitably uses titanium metal bipolar plates and noble metal catalysts, resulting in an increase in cost. The alkaline water electrolysis technology currently occupies the dominant position in the market due to its mature technology and low hydrogen production cost.

[0004] The diaphragm is a core component of the electrolytic cell, which has the function of allowing ions in the internal circuit to move freely and isolating H2 and O2 generated during the electrocatalytic processes of the anode and cathode. The presence of the diaphragm helps to reduce the energy consumption of the electrolytic cell and improve the safety of the electrolytic cell. The quality of the diaphragm has a restrictive effect on the purity of H2 and the electrolysis energy consumption, and directly determines the quality of the electrolytic water equipment. Therefore, the alkaline water electrolysis cell diaphragm should meet the following requirements: (1) H2 and O2 molecules cannot penetrate the diaphragm, but ions in the electrolyte are allowed to pass through; (2) It can resist the corrosion of high-concentration alkaline solutions; (3) It has good thermal stability and mechanical strength, and its structure is not damaged during long-term immersion in the electrolyte and flushing by H2 and O2 at the electrolysis temperature; (4) To reduce energy consumption, the diaphragm must have a small surface resistance, so the hydrophilicity of the diaphragm should be as high as possible; (5) The raw materials are easily available and non-toxic and pollution-free. Summary of the Invention

[0005] To solve the problems of high resistance and high energy consumption of polyphenylene sulfide fabrics, as well as the poor hydrophilicity and easy detachment of inorganic fillers in current composite diaphragms, the present invention provides a composite diaphragm based on superhydrophilic electrostatic self-assembly materials and a preparation method thereof.

[0006] The preparation method of the composite diaphragm based on superhydrophilic electrostatic self-assembly materials is as follows: Drop the positively charged inorganic nanoparticle dispersion into the negatively charged inorganic nanoparticle dispersion, stir for 1 - 3 h for electrostatic self-assembly to obtain a composite material, centrifuge, dry, and grind, then add it to the polymer solution, and perform ultrasonic stirring for 12 - 30 h to obtain a uniform casting solution; Scrape the casting solution on both sides of the sulfonated polymer mesh support layer, and solidify it into a film through pre-evaporation and phase inversion processes to obtain the composite diaphragm of superhydrophilic electrostatic self-assembly materials.

[0007] The preparation method of the sulfonated polymer mesh support layer is as follows: Immerse the polymer mesh support layer in concentrated sulfuric acid, perform sulfonation reaction at 40 - 80 °C for 30 - 60 min, then wash and dry.

[0008] The polymer support layer is selected from at least one of polyphenylene sulfide (PPS), polypropylene (PP), polyethylene (PE), and polytetrafluoroethylene (PTFE).

[0009] The mesh size of the polymer mesh support layer is 0.2 cm × 0.2 cm - 0.3 cm × 0.3 cm, and the thickness of the mesh fibers is 100 - 150 μm.

[0010] The negatively charged inorganic nanoparticles are selected from one or more of ZrO2, CeO2, SiO2, and titanates, preferably titanates.

[0011] The positively charged inorganic nanoparticles are layered double metal hydroxides, where the high-valence ions are selected from one or more of Fe 3+ , Al 3+ , Ti 4+ , and the low-valence metal ions are selected from one or more of Ni 2+ , Mg 2+ , Zn 2+ , Co 2+ , preferably NiFe-LDH.

[0012] The mass concentration of the positively charged inorganic nanoparticle dispersion and the negatively charged inorganic nanoparticle dispersion is 0.1 - 2 mg / mL, preferably 0.5 mg / mL.

[0013] The mass ratio of the positively charged inorganic nanoparticle dispersion to the negatively charged inorganic nanoparticle dispersion is 0.5 - 2.

[0014] The dropping rate is 5 - 15 mL / min.

[0015] The polymer solution is obtained by dissolving a binder and a pore former in an organic solvent, wherein the concentration of the binder is 100 - 300 mg / mL and the concentration of the pore former is 10 - 50 mg / mL.

[0016] The organic solvent is selected from at least one of N-methylpyrrolidone (NMP), N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), and dimethyl sulfoxide (DMSO).

[0017] The binder is selected from at least one of polysulfone (PSU) and PTFE.

[0018] The pore former is selected from at least one of polyvinylpyrrolidone (PVP) and polyethylene glycol (PEG).

[0019] In the casting solution, the mass ratio of the sum of the masses of the binder and the pore former to the mass of the composite material is 5 - 6:4 - 5.

[0020] The pre-evaporation is carried out at 60 - 80 °C for 5 - 30 min.

[0021] The phase inversion is carried out in deionized water for 30 - 120 s, preferably 60 - 90 s.

[0022] Application of the composite separator prepared above based on the superhydrophilic electrostatic self-assembly material as a separator in alkaline water electrolysis. The conditions of the alkaline water electrolysis are: in a 20 - 40 wt% potassium hydroxide or sodium hydroxide solution at 60 - 80 °C.

[0023] The present invention uses a sulfonated polymer grid as the support layer of the composite separator, which not only enhances its compatibility with the casting solution during the film-making process but also increases the mechanical strength of the composite separator. Then, a metal oxide or titanate inorganic filler and a layered double metal oxide are compounded by electrostatic self-assembly to prepare a superhydrophilic composite material. Using this composite material as a filler solves the problem of uneven mixing of several substances in the casting solution. The composite material has ultra-high hydrophilicity, and as an inorganic filler, it can reduce the filling ratio of the filler in the composite separator. The inorganic filler is almost completely coated by the binder, reducing the possibility of the inorganic filler falling off, thereby increasing the service life of the separator. The composite separator obtained by the present invention has excellent pore structure and surface hydrophilicity, good thermal stability and mechanical strength, and can sustain stable electrolysis for more than 300 h at a current density of 500 mA·cm -2 and can withstand the high-temperature alkaline electrolyte environment for a long time, has good water electrolysis performance and can function for a long time, has a long service life, and meets the actual industrial requirements. Description of the Drawings

[0024] Figure 1 is the preparation flow chart of the composite diaphragm; Figure 2 are the SEM images of the surface and cross-section of Example 1; Figure 3 are the area resistance data of the composite diaphragms prepared in Example 1, Example 2, Example 3 and Comparative Example 1; Figure 4 are the porosity, surface hydrophilicity, alkali absorption rate and area resistance data of the composite diaphragms prepared in Example 4, Example 5, Example 6 and Comparative Example 2; Figure 5 is the alkali stability test of Example 1; Figure 6 is the durability test of the composite diaphragm prepared in Example 1 when applied in an alkaline water electrolyzer. Detailed implementation manners

[0025] To make the objectives, technical solutions and advantages of the present invention clearer, the technical solutions of the present invention will be described in detail below. The following examples are convenient for better understanding of the present invention, but do not limit the present invention. The experimental methods in the following examples are all conventional methods unless otherwise specified.

[0026] All the reagents used in the present invention are purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. Example 1

[0027] (S1) A PPS grid support layer of 4×4 cm (grid size is 0.3 cm×0.3 cm, and the grid fiber thickness is 125 μm) is reacted in 16 mL of concentrated sulfuric acid at 50 °C for 0.5 h, and then washed and dried.

[0028] (S2) 600 mg of sodium titanate is ultrasonically dispersed in 300 mL of water and denoted as A; 300 mg of NiFe-LDH is ultrasonically dispersed in 150 mL of water and denoted as B. B is added to A at a dropping rate of 10 mL / min, and after the dropping is completed, it is stirred for 2 h; (S3) 750 mg of PSU and 75 mg of PVP are dissolved in 5 mL of NMP. After complete dissolution, 750 mg of the composite material prepared in (S2) is ultrasonically treated for 0.5 h and stirred for 24 h to prepare a uniform casting solution.

[0029] (S4) The casting solution described in step (3) is uniformly scraped onto both sides of the sulfonated PPS grid support layer of step (S1) by using a 750 μm coating applicator, and then placed in an oven at 60 o °C for pre-evaporation for 8 min. After pre-evaporation, it is placed in deionized water for phase inversion and cured into a film after 60 s.

[0030] Figure 1 It is a flow chart for the preparation of the composite separator. Figure 2 They are the surface and cross-sectional SEM images of Example 1. It can be seen that the inorganic filler is almost completely coated by PSU and there are a large number of finger-like pore structures in the cross-section, which are beneficial to the ion transport. Figure 3 They are the data of porosity, surface hydrophilicity, alkali absorption rate and area resistance of the composite separators prepared in Example 1, Example 2, Example 3 and Comparative Example 1. It can be seen that as the composite ratio of NiFe-LDH in the composite material increases, the pore structure of the prepared composite separator is better, the hydrophilicity is stronger, and the area resistance is lower. Figure 4 The area resistance data of the composite separators prepared in Example 4, Example 5, Example 6 and Comparative Example 2. Figure 5 It is the alkali stability test of Example 1. After being soaked in 30 wt% KOH at 80 o °C for 77 days, the inorganic filler did not fall off significantly and the surface resistance remained stable, proving its excellent alkali stability. Figure 6 It is for Example 1 applied in the electrolyzer to conduct the durability experiment at a current density of 500 mA·cm -2 , proving that the composite separator prepared in the present invention also has good durability in practical applications.

[0031] Example 2 Other conditions and operations are the same as those in Example 1. The difference is that in step (S2), 450 mg of sodium titanate is ultrasonically dispersed in 225 mL of water and denoted as A; 450 mg of NiFe-LDH is ultrasonically dispersed in 225 mL of water and denoted as B. B is added to A at a dropping rate of 10 mL / min, and after the dropping is completed, it is stirred for 2 h. Example 3

[0032] Other conditions and operations are the same as those in Example 1. The difference is that in step (S2), 300 mg of sodium titanate is ultrasonically dispersed in 150 mL of water and denoted as A; 600 mg of NiFe-LDH is ultrasonically dispersed in 300 mL of water and denoted as B. B is added to A at a dropping rate of 10 mL / min, and after the dropping is completed, it is stirred for 2 h. Example 4

[0033] Other conditions and operations are the same as those in Example 1. The difference is that in step (S2), sodium titanate is replaced by CeO2. Example 5

[0034] Other conditions and operations are the same as those in Example 2. The difference is that sodium titanate is replaced by CeO2. Example 6

[0035] Other conditions and operations are the same as those in Example 3. The difference is that sodium titanate is replaced by CeO2. Comparative Example 1

[0036] Other conditions and operations were the same as those in Example 1, except that in step (S3), 900 mg of pure sodium titanate was used as the inorganic filler to prepare the composite separator. Comparative Example 2

[0037] Other conditions and operations were the same as those in Comparative Example 1, and pure CeO2 was used as the inorganic filler to prepare the composite separator.

[0038] The composite separators of the above examples and comparative examples were characterized and performance-tested. The test items and methods are as follows: Morphology and structure: The separator was adhered to the conductive adhesive, and the morphology was characterized by a scanning electron microscope.

[0039] Porosity: The porosity of the composite separator represents the percentage of the pore volume of the composite separator in the volume of the composite separator, and is measured by the weighing method. Take 3 pieces of the composite separator and cut them into 20 mm×20 mm sizes, and record the area A of the composite separator sample. The composite separator sample was fully wetted with water, the surface moisture was wiped off with filter paper, weighed and recorded as G1 (accurate to 0.001 g), and the thickness of the composite separator sample was measured and recorded as d. Then it was fully dried in a vacuum drying oven at 60 o °C and weighed and recorded as G2 (accurate to 0.001 g). Then the porosity C of the composite separator was calculated by the following formula: , where: C is the porosity of the composite separator (%); G1 is the mass of the wet film of the composite separator (g); G2 is the mass of the dry film of the composite separator (g); is the density of deionized water (g / m 2 ); A is the area of the composite separator (m 2 ); d is the thickness of the wet film of the composite separator (m).

[0040] Contact angle: The contact angle is used to evaluate the hydrophilicity of the composite separator. The smaller the contact angle, the more hydrophilic the composite separator is, and it can contact the electrolyte more closely. The contact angle test was measured by a German Kruss DSA100 contact angle test system. The 20 mm×20 mm dry composite film was laid flat on the glass slide, and then 5 μL of deionized water was slowly dropped onto the surface of the composite separator using a syringe. The photo of the droplet just contacting the surface of the composite separator was captured, and the outer shape curve of the droplet in the image was fitted to calculate the contact angle.

[0041] Alkali absorption rate: The alkali absorption rate of the separator was measured with reference to the national electronic industry standard SJ-T 10171.7-1991. Cut the separator into test specimens of 20 mm×20 mm, with a total of 3 pieces. Wash and soak the cut test specimens 3 times with deionized water, and then place them in a vacuum drying oven at 50°C for sufficient drying. Weigh the test specimens, accurate to 0.001 g. Immerse the test specimens in a 30% analytical pure potassium hydroxide solution for more than 4 h. Use forceps to hold one corner of the test specimen and take it out of the alkali, suspend it for 30 s, drip off the alkali solution, and weigh it on a balance. (If there is a drop of alkali solution that has not dripped off, lean the corner of the test specimen with the liquid drop against the wall of the container to make the liquid drop fall off and then weigh it.) Take the average value measured from the 3 test specimens as the measurement result. The alkali absorption rate A is calculated by the following formula: , where: A —Alkali absorption rate of the separator (%); G 1 —Mass of the test specimen before alkali absorption (g); G 2 —Mass of the test specimen after alkali absorption (g).

[0042] Surface resistance: According to the test standard for the surface resistance of alkaline battery separators in the national electronic industry standard SJ / T 10171.5-1991 of the People's Republic of China, measure the surface resistance of the separator in a self-made surface resistance test device.

Claims

1. A preparation method of a composite separator based on a superhydrophilic electrostatic self-assembly material, characterized in that, The specific operation of the preparation method is as follows: Drop the positively charged inorganic nanoparticle dispersion into the negatively charged inorganic nanoparticle dispersion, stir for 1 - 3 h for electrostatic self-assembly to obtain a composite material, centrifuge, dry, and grind, and then add it to the polymer solution, and perform ultrasonic stirring for 12 - 30 h to obtain a uniform casting solution; Coat the casting solution on both sides of the sulfonated polymer mesh support layer, and solidify it into a film through pre-evaporation and phase inversion processes to obtain a composite separator of the superhydrophilic electrostatic self-assembly material.

2. The preparation method according to claim 1, characterized in that, The sulfonation method of the polymer mesh support layer is as follows: Immerse the polymer mesh support layer in concentrated sulfuric acid, carry out sulfonation reaction at 40 - 80 °C for 30 - 60 min, then wash and dry; The polymer support layer is selected from at least one of polyphenylene sulfide, polypropylene, polyethylene, and polytetrafluoroethylene.

3. The preparation method according to claim 1, characterized in that, The negatively charged inorganic nanoparticles are selected from one or more of ZrO2, CeO2, SiO2, and titanates, preferably titanates.

4. The preparation method according to claim 1, characterized in that, The positively charged inorganic nanoparticles are layered double metal hydroxides, where the high-valence ions are selected from Fe 3+ , Al 3+ , Ti 4+ and one or more of them, and the low-valence metal ions are selected from Ni 2 + , Mg 2+ , Zn 2+ , Co 2+ and one or more of them, preferably NiFe-LDH.

5. The preparation method according to claim 1, characterized in that, The mass concentration of the positively charged inorganic nanoparticle dispersion and the negatively charged inorganic nanoparticle dispersion is 0.1 - 2 mg / mL, preferably 0.5 mg / mL; The mass ratio of the positively charged inorganic nanoparticle dispersion to the negatively charged inorganic nanoparticle dispersion is 0.5 - 2.

6. The preparation method according to claim 1, wherein The polymer solution is obtained by dissolving a binder and a pore-forming agent in an organic solvent, wherein the concentration of the binder is 100 - 300 mg / mL, and the concentration of the pore-forming agent is 10 - 50 mg / mL; The organic solvent is selected from at least one of N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, and dimethyl sulfoxide; The binder is selected from at least one of polysulfone and PTFE; The pore-forming agent is selected from at least one of polyvinylpyrrolidone and polyethylene glycol.

7. The preparation method according to claim 6, wherein In the casting solution, the mass sum of the binder and the pore-forming agent and the mass ratio of the composite material is 5 - 6: 4 - 5.

8. The preparation method according to claim 1, wherein, The pre-evaporation is carried out at 60 - 80 °C for 5 - 30 min; The phase inversion is carried out in deionized water for 30 - 120 s, preferably 60 - 90 s.

9. Application of the composite separator based on the superhydrophilic electrostatic self-assembly material prepared by the method according to any one of claims 1 - 8 as a separator in alkaline water electrolysis.

10. The application according to claim 9, characterized in that, The conditions for the alkaline water electrolysis are: in a 20 - 40 wt% potassium hydroxide or sodium hydroxide solution at 60 - 80 °C.